2018
DOI: 10.1208/s12249-018-0966-7
|View full text |Cite
|
Sign up to set email alerts
|

Topical Niosome Gel Containing an Anthocyanin Complex: a Potential Oral Wound Healing in Rats

Abstract: Anthocyanins from dietary sources showing potential benefits as anti-inflammatory in oral lesions were developed as an anthocyanin complex (AC), comprised of extracts of Zea mays (CC) and Clitoria ternatea (CT), and formulated into a niosome gel to prove its topical oral wound healing in vitro and in vivo investigations. The AC formed nano-sized clusters of crystalline-like aggregates, occurring through both intra- and inter-molecular interactions, resulting in delivery depots of anthocyanins, following encaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…The free-radical-scavenging and antioxidant capacities of ANT pigments are introduced as the most highly recognized modes of action for interposing with numerous human therapeutic targets [17]. Moreover, with their anabolic effects in vivo , there is substantial verification suggesting that these phytochemicals have positive effects on wound healing [18]. In a previous study, ANT were found to promote wound healing by preventing oxidative damage [19]; however, to the best of our knowledge, the mechanisms by which ANT extracted from O. sativa L. act in modulating collagen formation and inflammation in skin fibroblasts have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The free-radical-scavenging and antioxidant capacities of ANT pigments are introduced as the most highly recognized modes of action for interposing with numerous human therapeutic targets [17]. Moreover, with their anabolic effects in vivo , there is substantial verification suggesting that these phytochemicals have positive effects on wound healing [18]. In a previous study, ANT were found to promote wound healing by preventing oxidative damage [19]; however, to the best of our knowledge, the mechanisms by which ANT extracted from O. sativa L. act in modulating collagen formation and inflammation in skin fibroblasts have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Different systems, such as ultradeformable liposome and noisome-based gels have been reported for their capacity to enhance the skin penetration, stability, and delivery of anthocyanins [ 84 ]. More recently, the release and skin permeation profiles of anthocyanins from a lipophilic delivery system were extensively studied in both porcine skin model and in human volunteers [ 194 ]. Two distinct lipstick formulations, one containing elderberry (mainly composed by simple glycosylated anthocyanins) and red radish (predominantly composed by larger anthocyanins exhibiting complex patterns of glycosylation and acylation) were tested to understand how the different structural patterns of anthocyanins might influence the skin permeation capacity.…”
Section: The Role Of Bioavailability For Anthocyanins Photoprotectmentioning
confidence: 99%
“…They have been a desireable drug delivery vehicle due to their simple and uniform preparation, low preparation costs, and relatively high shelf-life [13]. Because of these promising properties, niosomes have been used in a broad spectrum of applications ranging from topical and skincare treatments [4, 5], over oral and cancer therapies [6, 7], to gene deliveries [8, 9]. However, to further improve the functionality of niosomes, attentions have been drawn to their relatively lower bioavalibility and fast removal from the bloodstream [10, 11].…”
Section: Introductionmentioning
confidence: 99%